Biofeedback Therapy: An Overview - Hiebert, Bryan (Canadian Journal of Counselling and Psychotherapy, 2012)
The popularity of biofeedback has increased to the point where serious investigation by counsellor trainees and practitioners into the therapeutic claims and treatment methodologies of biofeedback training is warranted. In this paper the major therapeutic claims of biofeedback training and the respective methodologies used, are outlined, along with some of the research difficulties that are encountered in biofeedback training.